Classroom Design and Learning Environment as Predictors of Pre-Service Teachers’ Performance in Fine And Applied Arts in Colleges of Education in Southwestern Nigeria (2013)
Fine and applied arts provide the aesthetic and non-aesthetic necessities that enrich individuals’ quality of life. In recent times, the persistent students’ poor performance in the subject has been attributed to inadequate facilities, use of traditional classrooms and inappropriately designed learning environment in schools and institutions where teachers are being prepared. Researchers have focused on improved methodology and classroom practices but not on classroom and learning environment for teaching the subject. There is also a dearth of studies on influence of classroom design and learning environment on students’ performance in fine and applied arts. Most of the studies do not provide standardized classroom design and learning environment guidelines that could improve students’ performance in fine and applied arts. This study, therefore, determined the extent to which classroom design variables (spatial configuration, visual effects, thermal condition, acoustics factor, facilities and equipment) and learning environment variables (students’ perception, seats arrangement and class size) predicted pre-service teachers’ performance in fine and applied arts in colleges of education in Southwestern Nigeria. The study adopted the descriptive survey design. Two hundred and fifty final year fine and applied arts pre-service teachers and 70 lecturers selected through stratified random sampling technique participated in the study. They were drawn from 10 colleges of education purposively selected from Southwestern Nigeria. Instruments used were: Teachers’ Classroom Design Checklist, Teachers’ Classroom Acoustics Design Questionnaire (r=0.84), Lecturers Inventory for Facilities, Equipment and Materials, Learning Environment Questionnaire (r=0.81) and Teachers’ Fine and Applied Arts Performance Test (r=0.84). Nine research questions were answered and eight hypotheses tested at p<.05. Data were analysed using Pearson’s product moment correlation and multiple regression. The eight classroom design and learning environment variables taken together, have significant correlation with pre-service teachers’ performance in fine and applied arts (R=.407;F(8,249) =5.99; p<.05).They explained 13.8% of the variance in the dependent variable. The two factors that predicted pre-service teachers’ performance in fine and applied arts are facilities and equipment (β=1.088; t=4.43; p<.05) and seats arrangement (β =3.76;t=-3.19; p<.05). The five classroom design variables (spatial configuration, visual effects, thermal condition, acoustics factor, facilities and equipment) significantly correlated (R=.335; F(5, 244) = 7.03; p<.05) with pre-service teachers’ performance in fine and applied arts and explained 10.8% of the variance in the dependent variable. The three learning environment variables (students’ perception, seats arrangement and class size) correlated significantly (R=.23;F(3,249)=6.11;p<.05) with performance in fine and applied arts and 5.8% of the variance was due to the three factors. Seats arrangement had the highest relative contribution (β=.21). Out of the eight factors, four had significant relationships with the dependent variable. These are: acoustic factor (r= .154;p<.05), facilities and equipment (r=.284p<.05), students’ perception (r=.147;p<.05) and seats arrangement(r=-.222;p<.05). Facilities and equipment as well as seats arrangement predicted pre-service teachers’ performance in fine and applied arts. Hence, the use of adequately designed classroom and appropriate learning environment has become necessary. Therefore, appropriately designed art classrooms and relevant facilities should be provided to enhance performance in fine and applied arts in Nigerian colleges of education